Comparison of Lipids and Volatile Compounds in Dezhou Donkey Meat with High and Low Intramuscular Fat Content - Qingshan Ma; Xiyan Kou; Youyou Yang; Yunshuang Yue; Weihai Xing; Xiaohui Feng; Guiqin Liu; Changfa Wang; Yan Li (Foods, 2023)
The intramuscular fat (IMF) content is considered an important factor for assessing meat quality, and is highly related to meat flavor. However, in donkey meat, the influences of IMF content on lipid and volatile profiles remain unclear. Thus, we conducted lipidomic and volatilomic investigations on high- and low-IMF samples from donkey longissimus dorsi muscle. When the IMF level increased, the monounsaturated fatty acid (especially oleic acid) content significantly increased but the saturated fatty acid content decreased (p < 0.05). Twenty-nine of 876 lipids showed significant differences between the two groups. Volatile profiles from differential IMF content samples were also distinct. Five differential volatile odorants were identified in the two groups: 2-acetyl-2-thiazoline, octanal, 2-pentylfuran, pentanal, and 1-(2-pyridinyl) ethanone. Additionally, strong correlations were found between differential fatty acids and lipids with differential odorants. Thus, the difference in volatile odorants may result from the change in the fatty acid composition and lipid profiles induced by different IMF contents, highlighting the urgent need to increase IMF levels in donkey meat.